Analyzing Bacterial Species from Different Environments Using Direct 16S rRNA Gene Sequencing Methods - Faniyan, Olubunmi; Akpe, Victor; Cock, Ian E (Pharmacognosy Communications)
Multiple bacterial species including Escherichia coli, Bacillus spp., Streptococcus spp., Proteus spp., Pseudomonas aeruginosa, Serratia spp., Staphylococcus aureus, Enteroccus faecalis and Klebsiella spp. were collected and isolated from multiple geographical niches of Ado-Ekiti, Ekiti state in Nigeria. 16S ribosomal RNA (rRNA) gene sequencing analysis was applied using two universal primers. The bacterial isolates had similarity scores ≥ 96% when compared with the sequence-based bacterial type isolates in the GenBank of the National Center for Biotechnology Information (NCBI). The similarity score values were subsequently used to identify the bacterial isolates to genus and species levels. Thus, the inter-specific polymorphisms of the universal primer of the16S rRNA gene among different genera were found to be suitable for this study. Comparison of bacterial 16S rRNA gene sequences has emerged as a preferred genetic technique compared to the phenotypic identification of bacteria based on cell morphology, gram's reaction, colony morphology, catalase test, sporulation tests, gas production from glucose, e.t.c, and its validity in identifying bacterial species from different environments is verified in this study.
Keywords: Bacterial species identification; 16S rRNA; Universal primers; Similarity score values; Polymorphisms; Gene sequences